Determination of K shell parameters of silver using high resolution HPGe detector spectrometer. (1st January 2013) - Niranjana, K.M.; ,; Badiger, N.M.; Joseph, Daisy; Kailas, S.
The K shell parameters such as K shell photoelectric cross-section at K shell binding energy, K shell jump ratio, K shell jump factor, the Davisson- Kirchner ratio and K shell oscillator strength of silver have been determined using high resolution HPGe detector coupled to 16K multichannel analyser. In this method the K X-ray photons in the energy region from 8 to 52 keV are generated by sending 59.56 keV gamma photons from Am-241 source on various targets. These X-ray photons are allowed to pass through a silver foil in good geometry arrangement. By measuring the intensities of incident and transmitted photons, the mass attenuation coefficients are determined at various X-ray energies. Measured mass attenuation coefficient around K shell binding energy and K shell parameters have been compared with values predicted by XCOM and FFAST and with other experimental values.